(untitled) - Boser, Ursula (London, 2001)
This innovative language course uses liaison interpreting to teach spoken German to advanced students. Designed to provide an alternative to conversation classes, it is a highly effective aid to language acquisition and consolidation. Interpreting German will improve students' confidence in speaking and discussing a wide variety of contemporary topics
Keywords: German language,German language,German language; Spoken,English,English